Universal and Regional Standards for International Legal Protection of Refugees- De Lege Lata and De Lege Ferenda Evaluation - Agata SZWED (Communications of International Proceedings, 2020)
The aim of the article is to analyse and evaluate international legal protection of refugees at the universal and regional level, and on this basis to provide de lege lata comments and de lege ferenda postulates within the discussed scope. The hypothesis framed at the beginning of the article is a conclusion that the current standards for international legal protection of refugees do not ensure sufficiently effective protection to them. The key concept resulting from the subject of the paper is defined, followed by basic legal acts that create the standards for refugee protection, and then their evaluation is made. The analysis allows for the formulation and justification of conclusions regarding possible future changes in the applicable legislation. Two basic methods of legal science are employed in the article: dogmatic research method and legal comparison method. It can be concluded on the grounds of the conducted research that neither universal nor regional standards of refugee protection are sufficiently effective instruments for respecting the fundamental rights and freedoms of this group of people. The main drawbacks are that the Convention Relating to the Status of Refugees has not been adapted to the current global migration situation. The limitations of acts at regional levels and their often non-binding nature make it difficult to introduce uniform international procedures. The changes suggested in the article help to strengthen the level of protection of refugees and make an attempt to alleviate any negative effects in terms of the phenomenon of displaced persons.
Keywords: Refugees; International Refugee Law; International Law.